Efektivitas Monitoring Pelaporan Transaksi Asuransi Secara Real-Time Dengan Berbasis Website - Irfan Nurdiansyah; Reni Utami (STEKOM PRESS, 2025)
The insurance business in an insurance company offers insurance products owned by insurance companies. There are many transactions such as the purchase of insurance products and the application of disbursement of insurance benefits to customers, so that disputes occur in the reports generated every month and this does not become effective and time-efficient as needed. This study aims to evaluate the effectiveness of a website-based real-time insurance transaction reporting monitoring system. This research method involves the development of a web-based system designed to monitor and report insurance transactions directly, as well as the evaluation of system performance using quantitative and qualitative approaches. The research stages include needs analysis, system design and development, implementation, and system testing and evaluation in insurance companies. The results of the study show that a website-based system can facilitate evaluation Monitoring the results of reports on ongoing transactions, so that reports every month can be formed digitally through the system that has been created.